A Brief Introduction to Quranic Exegesis - Mobeen Vaid (International Institute of Islamic Thought, 2018)
Ali Suleiman Ali’s A Brief Introduction to Quranic Exegesis provides a lucid summary of the Quranic exegetical genre, beginning with the exegetical practices of the Prophet’s Companions and concluding with modern exegetical trends. Drawing largely from classical Sunni literature, Ali’s work is confessional but nonetheless conversant with Orientalist examinations and critical treatments of the tradition. In his introduction, Ali states that he intended to provide something “brief and descriptive not analytical,” which is an accurate characterization of the work. It is considerably more detailed than the cursory summary included in Von Denffer’s popular Ulum al-Quran, while retaining an accessibility for undergraduate and graduate students gaining initial exposure to the Quranic text and its concomitant explanations ...